The Role of Microglia and the Nlrp3 Inflammasome in Alzheimer's Disease - Hanslik, Kendra L.; Ulland, Tyler K. (Frontiers in Neurology, 2020)
Alzheimer's disease (AD) is the most prevalent form of late-onset dementia. AD affects the health of millions of people in the United States and worldwide. Currently, there are no approved therapies that can halt or reverse the clinical progression of AD. Traditionally, AD is characterized first by the appearance of amyloid-β (Aβ) plaques followed by the formation of intraneuronal neurofibrillary tangles (NFTs) composed of hyperphosphorylated tau (p-tau). These lesions are linked to synapse loss and eventual cognitive impairment. Additionally, microgliosis is consistently found in regions of the brain with AD pathology. The role of microglia in AD onset and progression remains unclear. Several recent reports indicate that the assembly of the multi-protein complex known as the NOD, LRR, and pyrin-domain containing 3 (Nlrp3) inflammasome by microglia results in apoptosis spec-like protein containing a CARD (Asc) spec formation, which then nucleates new Aβ plaques, thus amplifying Aβ-associated pathology. NFTs can also activate the Nlrp3 inflammasome leading to enhanced tau-associated pathology. Here, we will review the role of microglia and the activation of the inflammasome in the innate immune response to AD.